Radikalisme Islam di Jantung Kota Santri: Fragmentasi dan Polarisasi - Aripudin, Acep (STAI AL-FALAH CICALENGKA, 2020)
Tasikmalaya has a problem with the emergence of hardline Islamic movements, which sometimes bring out the face of